SISTEM PAKAR DIAGNOSA PENYAKIT SINDROM KLINEFELTER MENGGUNAKAN METODE BAYES - Sihombing, Darma Taksiah; Hasibuan, Nelly Astuti; Saputra, Imam; Fadlina, Fadlina (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
The development of computer-based medicine has increased in every generation. Health problems handled by doctors can now be accessed by anyone through the computer, one of them with the development of Expert System, the work of doctors facilitated. One of the health problems such as changes in physical men who resemble the physical woman is often a scary specter for some ordinary people. Not a few men change their true self to become a woman with the operation in neighboring countries such as Malaysia, Vietnam and even the Netherlands. Without realizing it these changes are actually closely related to the excess chromosomes found in genes in the blood. For that various symptoms or signs such as small testes, enlarged breasts like women and other complaints are a symptom of Klinefelter's Syndrome.